Analisis Pengaruh Kebijakan Promotional Mix Terhadap Nilai Tabungan Nasabah - Talung Wardana; Mulyadi Mulyadi; Santi Nururly (Postgraduate, University of Mataram, 2020)
The purpose of this study was to determine the level of significance of Promotional mix activities on the value of customer savings at PD. BPR. LKP Kotaraja (East Lombok) and to find out which promotional tools have a greater influence on the value of customer savings at PD. BPR. LKP Kotaraja (East Lombok). This type of research is descriptive research. The data collection method used is a case study. Data collection techniques by interview and documentation. The analysis tool used is multiple linear regression. From the results of data analysis, the regression equation Y = -1850682618 + 433.402X¬¬1 + 90.036X2 is obtained. Multiple linear correlation coefficient of 0.995. The coefficient of determination is 0.990, meaning that it is 99 percent of the value of customer savings in PD. BPR. LKP Kotaraja (East Lombok) can be explained by the cost of the promotion mix. Based on the analysis of the partial determination coefficient, it was obtained a value of 0.962 (96.2%) for personal selling and for sales promotion of 0.670 (67%). After the F test is carried out, it is obtained that the F count is 98.779 with an F table of 19.00. For the t test, respectively, the values were 7.192 for personal selling and 2.020 for sales promotion costs. The results showed that the personal selling activity and sales promotion simultaneously had a significant effect on the value of customer savings at PD. BPR. LKP Kotaraja (East Lombok). Personal selling activity has a significant effect (7,192> 4,303) on the value of customer savings at PD. BPR. LKP Kotaraja (East Lombok). That personal selling activities provide a greater influence than sales promotion activities